PERANAN GURU SEBAGAI SUPERVISOR KELAS TERHADAP KELANCARAN PROSES BELAJAR MENGAJAR - Syafrawi, Syafrawi (Universitas Islam Madura, 2019)
Efforts to improve the quality of education always require sustained conditions of high discipline in addition to requiring energy, costs and time to achieve the expected goals. Education lasts a lifetime, therefore education is a shared responsibility between the government, family and society. Of the three educational environments it is an integral part of achieving these objectives ranging from kindergartens to tertiary education both private and public. according to the term Indonesian is